2002
DOI: 10.1034/j.1600-0447.2002.9028.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of affective disorders, anxiety disorders, and non‐natural mortality in women after breast cancer diagnosis: a nation‐wide cohort study in Denmark

Abstract: Breast cancer patients have significantly increased incidence of psychiatric admission with affective disorders, anxiety disorders, and non-natural mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
1
23
1
3
Order By: Relevance
“…In a subsequent study by the same authors, exercise was again reported to be effective and to have a lower relapse rate (Babyak et al 2000). Specifi c to the importance of mood to breast cancer, a Danish study reported that those breast cancer patients who had been hospitalized for depression were signifi cantly more likely to die of breast cancer than women matched for the same stage of breast cancer but who had not been hospitalized for depression (Hjerl et al 2002). Even mild depression may hinder women from adherence to medical treatment for breast cancer, and hence survival (Somerset et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study by the same authors, exercise was again reported to be effective and to have a lower relapse rate (Babyak et al 2000). Specifi c to the importance of mood to breast cancer, a Danish study reported that those breast cancer patients who had been hospitalized for depression were signifi cantly more likely to die of breast cancer than women matched for the same stage of breast cancer but who had not been hospitalized for depression (Hjerl et al 2002). Even mild depression may hinder women from adherence to medical treatment for breast cancer, and hence survival (Somerset et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The number of people who live with the aftereffects of cancer and its treatment-disability, fear of recurrence, and economic burden-is growing (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Factors related to suicide include mainly clinical characteristics such as age at diagnosis (6,21), prognosis (5), psychiatric status (21,22), stage (1,3,6), time since diagnosis (1,6,21), and period of diagnosis (1,(4)(5)(6), and sociodemographic characteristics such as sex (1,3), race (1,21), and marital status (1,3,21).…”
Section: Introductionmentioning
confidence: 99%
“…Auch in anderen Arbeiten wie z. B. von Voigtmann et al [26] und Hjerl et al [13] zeigten sich ähnliche Ergebnisse.…”
Section: Diskussionunclassified